ARCHITECTURE AND BUILDING - Doliev Temur Kholbuta ugli; Khayriddinova Munisa Nizomiddin kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Architecture is the art and science of designing and constructing buildings and other physical structures. It blends creativity, engineering, and cultural expression to create spaces that serve functional, aesthetic, and social purposes. Architecture is the discipline of designing and constructing physical spaces that meet human needs while also considering aesthetics, functionality, and sustainability. It plays a vital role in shaping the built environment, reflecting societal values, cultural history, and technological advancements.